Multi-walled carbon nanotubes grow under low pressure hydrogen, air, and argon ambient by arc discharge plasma. Issue 4 (3rd April 2017) - Roslan, M. S.; Chaudary, K. T.; Haider, Z.; Aziz, M. S.; Ali, J.
ABSTRACT: Multi-walled carbon nanotubes (MWCNTs) were grown on cathode deposit by arc discharge plasma under H2, Ar, and air ambient environment. The influence of ambient gas pressure on the structure and physical properties of carbon nanotube were compared. Herein, we highlight the influence of ambient environment and pressure to grow high quality carbon nanotubes. Field emission scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, and X-ray diffraction were used for structural characterization and yield determination. The result revealed that background gas and pressure were crucial factor for growing highly crystalline and highly graphitic with ID /IG ratio 0.237 obtained for MWCNTs' synthesized in H2 environment with extreme low defects.